Sacred Sites in the Sakha Epics (Olonkho) and in Other Shamanic Traditions - M. M. Balzer (Oriental Studies, 2018)
This essay identifies descriptions of sacred lands within the Sakha (Yakut) olonkho, and compares them to mythopoetic honoring of sacred mountains among the Tlingit of Alaska and the Mapuche of Chile and Argentina. The olonkho of Niurgun Bootur, Kulun Kullustuur, Kyys Di϶b϶liye, and Эr Sogotokh are featured. Sacred site depictions in olonkho range from the fantastic and metaphorical to the more realistically descriptive and named. Given that many epics were composed before Uraangkhai Sakha ancestors arrived in territories of the Far North, it is difficult to identify specific sites with known current geography, although some Sakha scholars have tried. The Sakha olonkho depicts a well-known cosmology describing three worlds - Upper, Middle, and Lower. But what more specifically constitutes sacred geography? Natural criteria (mountains, lakes, rivers, meadows and trees), as well as characteristics of beauty within the Middle World, are revealed in olonkho. Rituals such as summer solstice ceremonies, yђyakh, and spirit offerings made with blessing prayers, algys, are associated with sacred sites. It is significant that many olonkho end with grand finales depicting these special places and rituals. I argue that “sacred land” ritual spaces of other indigenous peoples may be comparable to sacred spirit offering groves and special yђyakh sites, and that efforts to preserve sacred lands for contemporary rituals are part of ongoing cultural revitalization projects tied to ecological and spiritual consciousness in places with significant shamanic legacies.